Management of Small Unruptured Intracranial Aneurysms: To Treat or Not to Treat?. Issue 1 (January 2021) - Elkun, Yuval; Cooper, Jared; Kamal, Haris; Dakay, Katarina; Nuoaman, Halla; Adnan, Yasir Ammar; Dodson, Vincent; Nuoman, Rolla; Kaur, Kavneet; Kurian, Christeena; Sahni, Ramandeep; Gandhi, Chirag; et al.
Abstract : Unruptured intracranial aneurysms measuring <7 mm in diameter have become increasingly prevalent due to advances in diagnostic imaging. The most feared complication is aneurysm rupture leading to a subarachnoid hemorrhage. Based on the current literature, the 3 main treatments for an unruptured intracranial aneurysm are conservative management with follow-up imaging, endovascular coiling, or surgical clipping. However, there remains no consensus on the best treatment approach. The natural history of the aneurysm and risk factors for aneurysm rupture must be considered to individualize treatment. Models including population, hypertension, age, size of aneurysm, earlier subarachnoid hemorrhage from a prior aneurysm, site of aneurysm score, Unruptured Intracranial Aneurysm Treatment Score, and advanced neuroimaging can assist physicians in assessing the risk of aneurysm rupture. Macrophages and other inflammatory modulators have been elucidated as playing a role in intracranial aneurysm progression and eventual rupture. Further studies need to be conducted to explore the effects of therapeutic drugs targeting inflammatory modulators.